1989
DOI: 10.1002/zaac.19895760115
|View full text |Cite
|
Sign up to set email alerts
|

Zum Reaktionsmechanismus der Äquilibrierung im System SiCl4/Sil4 in Gegenwart von Pyridin

Abstract: Äquilibrierungsreaktionen zwischen SiCl4 und Sil4 in Gegenwart von Pyridin werden bei 343 K in Benzen über einen heterogenen Halogenaustausch zwischen gelösten Siliciumtetrahalogenidmolekeln und dem festen Fällprodukt Siliciumtetrahalogenid‐Pyridin‐Komplex realisiert. Durch die Koordination von Pyridin am Siliciumtetrahalogenid wird das in gleicher Koordinationssphäre befindliche kovalent gebundene Halogen gelockert und damit austauschbar, während ionogen gebundenes Halogen nicht am Austausch teilnimmt. Bei Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Elemental analysis of the substance as well as thermochemical observations revealed that less than the expected four equivalents of the nitrogen base reacted to form a complex. Dismutation of SiCl 2 I 2 (Hass et al, 1989) occurred during the preparation of the complex leading to a mixture of product complexes with varying stoichiometry with respect to halide distribution and silicon halide/methylpyridine ratio. We were able to crystallize two component complexes from the moderately soluble product powder: SiCl 4 (4-methylpyridine) 2 (Hensen, Mayr-Stein, Spangenberg & Bolte, 2000) and the title compound from a hot chloroform solution that was allowed to evaporate at room temperature under vacuum over two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Elemental analysis of the substance as well as thermochemical observations revealed that less than the expected four equivalents of the nitrogen base reacted to form a complex. Dismutation of SiCl 2 I 2 (Hass et al, 1989) occurred during the preparation of the complex leading to a mixture of product complexes with varying stoichiometry with respect to halide distribution and silicon halide/methylpyridine ratio. We were able to crystallize two component complexes from the moderately soluble product powder: SiCl 4 (4-methylpyridine) 2 (Hensen, Mayr-Stein, Spangenberg & Bolte, 2000) and the title compound from a hot chloroform solution that was allowed to evaporate at room temperature under vacuum over two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Am Beispiel der Reaktion zwischen Siliciumtetraiodid und -chlor id in Gegenwart von Pyridin konnte gezeigt werden, da13 der Halogenaustausch zwischen flussiger und fester Phase als Heterogenreaktion unter Einbeziehung der dabei gebildeten ionischen Siliciumchloridiodid-Pyridin-Komplexe verlauft[4]. Zum Austausch befahigt ist jedoch nur das am Silicium kovalent gebundene Halogen, wahrend ionogen gebundenes Halogen am Austausch nicht teilnimmt, so daB demZugleich wird das Auftreten einer festen Phase beobachtet, die nach Versuchsende abfiltriert und durch quantitative Bestimmung der Halogene summarisch als SiBr,CI, * 2 P y identifiziert werden kann.…”
unclassified